2015
DOI: 10.1089/biores.2014.0035
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in Cancer Stem Cells: A Potential Link Between Chemoresistance, Recurrence, and Metastasis

Abstract: Cancer cells require an uninterrupted nutritional supply for maintaining their proliferative needs and this high demand in concurrence with inadequate supply of blood and nutrition induces stress in these cells. These cells utilize various strategies like high glycolytic flux, redox signaling, and modulation of autophagy to avoid cell death and overcome nutritional deficiency. Autophagy allows the cell to generate ATP and other essential biochemical building blocks necessary under such adverse conditions. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
89
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 86 publications
0
89
0
1
Order By: Relevance
“…Furthermore, mounting evidences had suggested that activation of autophagy promoted chemoresistance 8, 36, 37 . On the other hand, we found that siRNA knocking down of BECN-1 or ATG5 could reduce the chemoresistance and reversed the effect of miR-140-5p, suggesting an important role of autophagy on chemoresistance and miR-140-5p increased the chemoresistance through miR-140-5p/HMGN5/autophagy regulatory loop.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mounting evidences had suggested that activation of autophagy promoted chemoresistance 8, 36, 37 . On the other hand, we found that siRNA knocking down of BECN-1 or ATG5 could reduce the chemoresistance and reversed the effect of miR-140-5p, suggesting an important role of autophagy on chemoresistance and miR-140-5p increased the chemoresistance through miR-140-5p/HMGN5/autophagy regulatory loop.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that the increased autophagy within HSC is necessary for lipid breakdown to provide the necessary energy source to undergo activation through the process of lipophagy (30). Such dichotomous findings are noted in cancer literature, where autophagy has been reported as both promotional and inhibitory for tumor growth (31)(32)(33)(34)(35). These divergent findings likely reflect the complexity of the role of autophagy in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…BCSCs have also been observed in vitro and in vivo to accumulate less DNA breaks after radiation [56]. Therefore, it is hypothesized that the traditional cancer therapies reduce tumor bulk, but the inability to completely eradicate BCSCs results in the failure of complete remission [54,56,57]. …”
Section: Breast Cancer Stem Cells and Radiationmentioning
confidence: 99%
“…Although numerous factors contribute to the characteristics of BCSCs, autophagy has been linked to BCSCs survival and resistance to therapy [57]. Previously, breast tumors injected with serum-deprived mesenchymal stem cells have demonstrated higher cellularity and decreased apoptosis, with increased levels of autophagic activity in the surrounding areas [59].…”
Section: Autophagy In Breast Cancer Stem Cellsmentioning
confidence: 99%